Use of the word barbekiu and its representation in the Dictionary of Standard Lithuanian - Murmulaitytė, Daiva (Taikomoji kalbotyra, 2014)
The new borrowing barbekiu has not been included into dictionaries of the Lithuanian language so far, except for the Dictionary of Internationalisms (2001, 2008) and its internet version Interleksis. Due to the frequent use of the word, barbekiu is going to be included into the Dictionary of Standard Lithuanian. The present paper analyses the semantic structure of the borrowing, its use and normative recommendations, investigates dictionary entries of barbecue and its synonym grill as given in a number of English, Latvian, Russian, and Polish dictionaries. The use of the borrowing barbekiu in the Lithuanian language shows a slightly different semantic structure of the word than that offered in the dictionaries of the donor (English) language. On the whole, the findings of this research show that the semantic structure of the borrowing barbecue in the recipient languages differs from its semantic structure in the English language. Finally, the paper offers several tentative dictionary entries for the word barbekiu and its Lithuanian equivalents, which could be included into the Dictionary of Standard Lithuanian. In addition to the two meanings of the word that have already been discussed by language planners (i.e. barbecue as a ‘baking device’ and as a ‘certain steak’), the proposed dictionary entries would contain additional, more frequent meanings: ‘a way of preparing a certain kind of food’ and ‘a party in which food is prepared in this way’.